Market Disruption and the Incidence of VERs Under the MFA - Dean, Judith M. (The Review of Economics and Statistics, 1995)
Market disruption or the threat thereof constitutes grounds for restraining countries under the U.S. Multifibre Arrangement (MFA). Since 1980, however, countries accounting for very small shares of U.S. imports have been restrained. This study estimates the determinants of U.S. voluntary export restraints under MFA I and MFA II-III using a bivariate probit model with sample selection. Results show a shift from targeting large developing country exporters to targeting those that are small but have rapidly growing sales. This raises the cost of the MFA to the United States. It also suggests that expansion of exports by developing countries will be met by restrictions on market access. Copyright 1995 by MIT Press.